Polar bears : survival on the ice - Viola, Jason (Science comics (First Second (Firm)), 2019)
Mama Polar Bear teaches her cubs, the curious sibling rivals Anik and Ila, what it means to be a polar bear as they move into the winter season and the cubs begin growing up to learn how to survive the ice and snow and hunt on their own.